2019
DOI: 10.1177/1179069519849935
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for the Development of Chronic Traumatic Encephalopathy From Persistent Traumatic Brain Injury

Abstract: A mechanism that describes the progression of traumatic brain injury (TBI) to end-stage chronic traumatic encephalopathy (CTE) is offered in this article. This mechanism is based upon the observed increase in the concentration of both tau protein and of human leukocyte antigen (HLA) class I proteins; the HLA increase is expressed on the cell membrane of neural cells. These events follow the inflammatory responses caused by the repetitive TBI. Associated inflammatory changes include macrophage entry into the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Repeated traumatic brain injury results in an increase in the levels of IL-1, which is produced by activated microglia, resulting in increased tau phosphorylation. In a post-mortem study of 66 cases of CTE and 16 controls, the dorsolateral frontal cortex showed higher levels of CD68 immunoreactive microglia ( Demock and Kornguth, 2019 ). Thus, CD68 was interpreted as being a potential therapeutic target for CTE.…”
Section: Tauopathy As a Cause Of Neuroinflammationmentioning
confidence: 99%
“…Repeated traumatic brain injury results in an increase in the levels of IL-1, which is produced by activated microglia, resulting in increased tau phosphorylation. In a post-mortem study of 66 cases of CTE and 16 controls, the dorsolateral frontal cortex showed higher levels of CD68 immunoreactive microglia ( Demock and Kornguth, 2019 ). Thus, CD68 was interpreted as being a potential therapeutic target for CTE.…”
Section: Tauopathy As a Cause Of Neuroinflammationmentioning
confidence: 99%
“…However, recently a role for HLA-DRB1 in tau processing in TBI has been suggested. Demock and Kornguth suggest that intracellular tau accumulation is driven by the binding of extracellular tau to membrane-bound HLA, which then undergoes endocytosis (Demock and Kornguth, 2019 ). Further research should be conducted to investigate this hypothesis and determine whether variations in HLA-DRB1 differentially affect tau processing in both AD and TBI contexts.…”
Section: Ad Genetic Risk Variants Associated With Microgliamentioning
confidence: 99%
“…Repetitive TBI can lead to end stage CTE. Several mechanisms responsible are elevated concentration of both tau proteins, human leu kocyte antigen (HLA) clas s I proteins, macrophage entry into brain parenchyma from disruption of BBB and microglial activation at the base of the sulci [84,85].…”
Section: Chronic Traumatic Encephalopathymentioning
confidence: 99%